Analisis Location Quotient (LQ) dan Model Rasio Pertumbuhan (MRP) Usaha Peternakan Sapi Potong di Provinsi Bengkulu - Azis, Arif Rahman; Hamka, Muhammad Subhan; Bilyaro, Woki; Dani, Muhammad (Buletin Peternakan Tropis, 2024)
The cattle industry has a strategic role in supporting food security and national economic growth. Bengkulu Province with sufficient area, a tropical climate suitable for feed growth, and adequate human resources is the main capital to support the beef cattle development sector. Location Quotient (LQ) and Growth Ratio Model (MRP) analysis approaches were used to evaluate the condition and development potential of this sector. Secondary data from 2018-2022 were analyzed using these methods. The results of the LQ analysis revealed significant variations in the specificity of the beef cattle sector across districts. Meanwhile, the MRP analysis showed that although the overall growth of the beef cattle population was not very prominent, some districts showed higher growth compared to the province as a whole. In conclusion, a targeted and contextualized development strategy is required to increase the beef cattle population in Bengkulu Province. Further research is needed to understand the factors underlying variations in beef cattle development potential and performance across districts and to develop innovative and environmentally friendly livestock technologies. With the right strategy, Bengkulu Province can increase its beef cattle population, improve the welfare of local farmers, and boost regional economic growth.   Key words: Beef Cattle, Bengkulu Province, Location Quotient, Growth Ratio Model   ABSTRAK Industri peternakan sapi potong memiliki peran strategis dalam mendukung ketahanan pangan dan pertumbuhan ekonomi nasional. Provinsi Bengkulu dengan luas wilayah yang cukup, iklim tropis yang cocok untuk pertumbuhan pakan, dan sumber daya manusia yang memadai menjadi modal utama untuk mendukung sektor pengembangan sapi potong. Pendekatan analisis Location Quotient (LQ) dan Model Rasio Pertumbuhan (MRP) digunakan untuk mengevaluasi kondisi dan potensi pengembangan sektor ini. Data sekunder dari 2018-2022 dianalisis menggunakan metode ini. Hasil analisis LQ mengungkapkan variasi signifikan dalam kekhususan sektor sapi potong di berbagai kabupaten. Sementara itu, analisis MRP menunjukkan bahwa meskipun pertumbuhan populasi sapi potong secara keseluruhan tidak terlalu menonjol, beberapa kabupaten menunjukkan pertumbuhan yang lebih tinggi dibandingkan dengan provinsi secara keseluruhan. Kesimpulannya, strategi pengembangan yang terarah dan kontekstual diperlukan untuk meningkatkan populasi sapi potong di Provinsi Bengkulu. Penelitian lebih lanjut diperlukan untuk memahami faktor-faktor yang mendasari variasi potensi dan kinerja pengembangan sapi potong di berbagai kabupaten, serta untuk mengembangkan teknologi peternakan yang inovatif dan ramah lingkungan. Dengan strategi yang tepat, Provinsi Bengkulu dapat meningkatkan populasi sapi potongnya, meningkatkan kesejahteraan peternak lokal, dan mendorong pertumbuhan ekonomi daerah.   Kata kunci: Sapi Potong, Provinsi Bengkulu, Location Quotient, Model Ratio Pertumbuhan.